2010
DOI: 10.1007/s10278-010-9293-6
|View full text |Cite
|
Sign up to set email alerts
|

Compare Display Schemes for Lung Nodule CT Screening

Abstract: This study investigated the relative efficiencies of a stereographic display and two monoscopic display schemes for detecting lung nodules in chest computed tomography (CT). The ultimate goal was to determine whether stereoscopic display provides advantages for visualization and interpretation of three-dimensional (3D) medical image datasets. A retrospective study that compared lung nodule detection performances achieved using three different schemes for displaying 3D CT data was conducted. The display modes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The ability to view only the brightest pixels helps to define smaller structures. This post processing technique has been used to identify vascular structures, pulmonary nodules, and ureteral stones in people and dogs, and is reported to improve abnormality detection rates as compared to axial source images alone . In addition, MIP images have been shown to provide greater reader confidence in detection of pulmonary nodules in a canine model .…”
Section: Introductionmentioning
confidence: 99%
“…The ability to view only the brightest pixels helps to define smaller structures. This post processing technique has been used to identify vascular structures, pulmonary nodules, and ureteral stones in people and dogs, and is reported to improve abnormality detection rates as compared to axial source images alone . In addition, MIP images have been shown to provide greater reader confidence in detection of pulmonary nodules in a canine model .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research into 3D medical imaging has found applications in ophthalmology, mammography, oncology, orthopedic studies, and vascular mapping among others [ 6 , 30 31 ]. Various modalities have been implemented for 3D stereoscopic imaging including X-ray, CT and visual imaging [ 32 36 ]. In detecting breast cancer lesions, Getty et al found a 44% decrease in false positives when utilizing stereoscopic mammography [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of stereoscopic display to view TS-MIPs has been shown to improve nodule detection and shorten interpretation time when compared to standard viewing (8), and the use of thin-slab volume rendering has been shown to significantly improve the detection of lung nodules relative to TS-MIP for nodules <11 mm in diameter (49). …”
Section: Image Based Methods For Performance Improvementmentioning
confidence: 99%
“…These guidelines are consistent with the CT techniques used in both the National Lung Screening Trial (NLST) and the NELSON trials (6, 7). When viewing transverse sections, image size, reader distance from the image, paging rate, and the use of stereoscopic display have been shown to influence lung nodule detection (810). This review focuses on issues concerning the assessment of reader performance for the identification of lung nodules, the current understanding of radiologist’s performance, and steps that have been investigated to improve radiologist performance in the identification of lung nodules in general and lung cancer in particular.…”
Section: Introductionmentioning
confidence: 99%